Strategi Mengelola Risiko dalam Kewirausahaan Belajaran Dari Kegagalan Awal Dari Keberhasilan - Yuni Tobe; Jindry Tafuli; Yosia Belo (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Entrepreneurship is an activity filled with challenges and risks but also offers opportunities for growth and innovation. In the business world, risk is inevitable and must be managed with effective strategies to achieve success. This article discusses various strategies that entrepreneurs can use to identify, manage, and mitigate risks to maximize the chances of success and minimize the impact of failure. Through a case study approach and comparative analysis of entrepreneurs' experiences with failure and success, this research highlights the importance of learning from experience to strengthen business resilience and enhance decision-making skills. The findings of this research are expected to serve as a reference for entrepreneurs in developing better risk management skills and strengthening the foundation for business sustainability. By understanding and applying adaptive and responsive risk management strategies, entrepreneurs can optimize their chances of success and reduce the potential for failure in a competitive business environment.